The study of Eimeria tenella infections in Poultry Birds in Ekiti State - Adewole, Samson; Odeyemi, Dolapo; Aleem, Serifat; T.E, Omoyeni (International Journal of Scientific World, 2017)
In developing countries, animal production is being subjected to great pressure to satisfy the demand for animal protein required by the continuous increasing human population and to have surplus for international trade. Coccidiosis is a major health problem of poultries. This aim of this study is to determine the prevalence of caecal coccidiosis infections in poultry birds in Ekiti State. Three poultry sites were randomly selected and studied in Ekiti state. 10,000 birds were examined out of which 1033 birds tested positive to coccidiosis infection. Test tube floatations for faecal content and wet smear preparation for the caecal lining were done to test the presence of Eimeria tenella(Et)based on the dimension of oocyst and respiratory disease respectively. The result showed the highest percentage of Et infection in Yomi poultry farms in Ifaki Ekiti representing 6.8% while Daac poultry farms had the least percentage of 3%. The percentage occurrence of respiratory disease is highest in Daac farms with 6% and a least percentage of 3% in Christ's power poultry. The result implies that there is a still presence of Et infections in the poultries considered for study in Ekiti, thus the need for biosafety measures, information and protection programs against the disease.